Association between admission lactate levels and mortality in patients with acute coronary syndrome: a retrospective cohort study. Issue 1 (January 2019) - Liang, Dongjie; Zhou, Xiaodong; Hong, Xia; Feng, Xiafei; Shan, Peiren; Xie, Qiangli; Xu, Tiancheng; Cai, Mengxing; Zhou, Jian; Wang, Songjie; Huang, Weijian
Abstract : Objective: Hyperlactatemia at admission is associated with poor outcome in critically ill patients. However, data on the prognostic value of blood lactate level in patients with acute coronary syndrome (ACS) are limited. The present study assessed the prognostic effect of admission lactate level in a large population of patients with ACS. Materials and methods: This was a retrospective observational study including patients with ACS who were admitted to the Coronary Care Unit of the First Affiliated Hospital of Wenzhou Medical University between 2014 and 2017. Patients were divided into tertiles of lactate level (T1: <1.8; T2: 1.8–2.6; T3: ≥2.7 mmol/l). The clinical outcomes were 30-day and 180-day mortality from hospital admission. Cox proportional hazards models were used to evaluate the association between lactate level and survival. Results: A total of 1865 consecutive patients with ACS were enrolled. Significant positive associations were observed between admission lactate level and both 180-day and 30-day mortality, with highest risk for lactate greater than or equal to 2.7 mmol/l. The adjusted hazard ratio for 180-day mortality was 2.09 [95% confidence interval (CI): 1.18–3.71, P =0.011] for T3 and 1.53 (95% CI: 0.86–2.72, P =0.147) for T2 compared with T1 ( P for trend=0.006), and 1.10 (95% CI: 1.02–1.18, P =0.010) for each unit increase in lactate level. Similar trends were observed for 30-day mortality. The association was highly consistent across all subgroups studied (all P for interaction >0.05). Conclusion: In patients with ACS, elevated admission lactate level is an independent predictor of 30-day and 180-day all-cause mortality. Abstract : Supplemental Digital Content is available in the text.